2007
DOI: 10.1111/j.1600-0420.2007.01062_3248.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of patients with late complications after filtering surgery

Abstract: Purpose: Demonstrate the possibilities of successful surgical treatment of patients with late complications after filtering surgery. Methods: This study shows patients who have developed a cystically dilated or leaking filtering bleb in the late post‐surgical period after filtering surgery. Excision of the indadequate filtering bleb has been performed in the patient with a cystic bleb. After the failure of less invasive methods of treatment, we have proceeded to bleb revision with a scleral patch graft in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…[9] However, since commonly used dexamethasone in the water-soluble form of phosphate ester (dexamethasone phosphate) is to be administered as eye drops multiple times a day for several weeks postoperatively, patient compliance plays a crucial role in treatment. [10,11] However, compliance with the regulated use of eye drops may be unpredictable in the elderly cataract surgery patient population. [12] Studies have reported non-adherence to regulated eye drop therapy ranging from 5% to 80%.…”
Section: Introductionmentioning
confidence: 99%
“…[9] However, since commonly used dexamethasone in the water-soluble form of phosphate ester (dexamethasone phosphate) is to be administered as eye drops multiple times a day for several weeks postoperatively, patient compliance plays a crucial role in treatment. [10,11] However, compliance with the regulated use of eye drops may be unpredictable in the elderly cataract surgery patient population. [12] Studies have reported non-adherence to regulated eye drop therapy ranging from 5% to 80%.…”
Section: Introductionmentioning
confidence: 99%